Valores no trabalho, identificação social e organizacional: o fio condutor para a permanência das mulheres em atividades laborais - Faller, Lisiane Pellini (2017)
Work has been the central element in the organization‟s life, in the social identity of individuals and in the identification of these people with their companies, constituting an agent of social relations important for unity perception or sense of belonging to the organization. The increase in the female presence in the civil construction sector has instigated an understanding of the behaviors and factors that explain women's interest in remaining in historic and male-dominated jobs. Thus, the general goal of this study was to analyze the interactions among the values related to work, the processes of social identification and organizational identification and the sense of belonging / permanence, from the perspective of working women in the construction industry. For that, an empirical qualitative and exploratory research was conducted with qualitative methodologies for the survey and analysis of the results. Initially, categories of analysis were defined a priori with elements of analysis corresponding to each category. After that, the interview scripts were elaborated, which were evaluated by specialists. The next step consisted of ten female construction workers interviews from four organizations, the application of the value disc and the organizational identification measurement chart. From the reports, the categories of ex post analysis were elaborated. For the data treatment, the content analysis technique, with interview transcripts was used as well filtering, organization and thematic categorization of the data. The main results show the relationship among values at work, social identification and organizational identification as conductive threads for the women‟s permanence in manly masculine jobs. It was observed that the organizations are contributing to the identification of women workers to jobs historically occupied by men, but there are still reports of discrimination regarding women's work in these sectors. The observations that emerge from the results of this research suggest that values at work and identification with social and organizational contexts assume central roles in encouraging women to stay in work environments.